Commissive Illocutionary Acts Found in Na’ima Robert’s She Wore Red Trainers - Al-Sharabi, Doa‘a Ali Mohammed Farhan; Al-Ghrafy, Abdusalam Mohammed Ghaleb (Journal of Humanities & Social Sciences, 2023)
This study aims to find out the commissive illocutionary acts which are implied by the characters in the novel She Wore Red Trainers (2014) by Na’ima Robert. It aims to identify the types of commissive illocutionary acts found in the selected novel. This study uses a descriptive- qualitative method to examine the collected data. The data are utterances collected from the text of the selected novel. These utterances are classified on the basis of on the speech act theories of Austin (1962) and Searle (1969), into three types of commissive illocutionary acts: offering, promising and refusing acts. The results of this study revealed that there are 10 utterances in She Wore Red Trainers novel: 5 offering utterances, 4 promising utterances and 1 refusing utterance. Since this study observes the commissive illocutionary acts in the novel to reveal their implied meanings, it is recommended that similar studies be conducted to examine commissive illocutionary acts in other fictions.
Keywords: speech acts; illocutionary acts; commissive illocutionary acts; She Wore Red Trainers